2016
DOI: 10.1186/s12889-016-3015-z
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter and atherosclerosis: a bibliometric analysis of original research articles published in 1973–2014

Abstract: BackgroundEpidemiological and experimental studies have suggested that exposure to particulate air pollution may promote progression of atherosclerosis.MethodsIn the present study, the characteristics and trends of the research field of particulate matter (PM) and atherosclerosis were analyzed using bibliometric indicators. Bibliometric analysis was based on original papers obtained from PubMed/MEDLINE search results (from 1973 to 2014) using Medical Subject Headings (MeSH) terms. A fully-detailed search strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…Numerous quantitative analysis methods have been utilized to study the research front issue, such as citation-related analysis [3][4][5][6][7][8][9][10][11] and content analysis [12][13][14][15][16][17][18][19][20]. With ample research results, citation analysis method started early, which can be concluded into co-citation analysis [5][6][7], bibliographic coupling [10,11], and direct citation [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous quantitative analysis methods have been utilized to study the research front issue, such as citation-related analysis [3][4][5][6][7][8][9][10][11] and content analysis [12][13][14][15][16][17][18][19][20]. With ample research results, citation analysis method started early, which can be concluded into co-citation analysis [5][6][7], bibliographic coupling [10,11], and direct citation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Content analysis is useful for understanding the knowledge in the literature. It includes term frequency analysis [15,18], burst term analysis [12], and co-word analysis [17,20]. With purpose of identifying research fronts in the field of MI, this study applied a topic model to quantitatively investigate scientific articles published in 26 MI journals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bibliometric techniques have been used to explore trends in research related to various scientific disciplines; such as lab-on-a-chip research [ 32 ], nanotechnology research [ 33 ], public health research [ 34 ], organic farming research [ 35 ], pluripotent stem cell research [ 36 ], particulate matter and atherosclerosis research [ 37 ], and Helicobacter pylori research [ 38 ]. Earlier research has shown that the same methods may be applied to clinical toxicology themes such as intravenous lipid emulsion as an antidote [ 39 ], methanol poisoning [ 40 ], and calcium channel blockers poisoning [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In areas with high ambient atmospheric pollution (which may originate from industry and construction sources), surges in dust content brought about by dust worsen the dust’s effect on health 4. PM is also known to result in cardiac arrhythmias, which can precipitate HF in the context of cardiovascular disease 34. Subclinical atherosclerosis has also been shown to result from PM ambient pollution and is reflected in carotid intima media thickness studies 35…”
Section: The Harmattan and Cardiovascular Diseasesmentioning
confidence: 99%